Punching above Gwynedd's weight: Llywelyn ap Gruffudd's diplomatic communication and the road to war in 1277. (1st December 2019) - Brodie, Hugh
The decade between 1267 and 1277 was crucial in Gwynedd's struggle to establish a native Welsh polity. It required a small territory with slender resources to mount diplomacy promoting Llywelyn's status as 'princeps Wallie' not merely with the English crown but with the papal curia. Llywelyn's diplomatic letters have hitherto been scrutinised for the light they shed on the course of events. This article examines instead their style and effectiveness as a mode of diplomatic communication. It compares them with diplomatic letters of Alexander III of Scotland and sheds light on how native Wales was interacting with Anglo-French culture. The analysis draws on a number of previouslyunpublished original documents, transcribed here for the first time, including Pope Gregory X's letter to Edward I in August 1274, inspired by Llywelyn, and preparatory drafts of Edward's letter to Llywelyn in May 1275.